Environmental quality and economic growth: Evidence from 10 ASEAN countries - Achmad Rifa'i; Nurvita Retno Dewi (Center for Science and Technology, IAIN Surakarta, 2018)
The environment is often regarded as affected by the economic activity. Many studies have attempted to prove the Environmental Kuznets Curve (EKC) phenomenon, but few aimed to look beyond the impact of environmental quality and its contribution to the economic growth. This research aims to fill the gap of the literature. ASEAN is a region which is currently trying to maximize the potential of its natural resources to increase the economy of the region. With the abundance of existing natural resources, it is expected to make the region as a new economic source in the world. Panel data from 10 countries from 1994-2015 was employed to look at the environmental impacts of the ASEAN region on economic growth. Empirical results indicated that population, forest area, and CO2 emissions significantly affect economic growth. Nevertheless, it is suggested to be more prudent in using existing resources to maintain the stability of the economic growth without sacrificing the environment that has the very essential importance in the human life.